(NsINTAKSIS SOWREMENNOGO HINDI (B/s - (NlIPEROWSKIJ(B, (NwLADIMIR pETROWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NWOST(B. (NLIT(B.,s, 1987)
(NbIBLIOGR(B.: (NS(B. 158-163 (143 (NNAZW(B.). (NbIBLIOGR(B. (NW PRIME^(B.: (NS(B. 154-157s
(Nan sssr(B, (NiN(B-(NT WOSTOKOWEDENIQs
Keywords: (NhINDI QZYK (B- (NsINTAKSISs